Aktivitas antihiperglikemia ekstrak kulit dan daun surian (Toona sinensis) pada tikus diabetes (Sprague-dawley) yang diinduksi streptozotocin - Theresia, Rori; Falah, Syamsul; Safithri, Mega (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
This study aimed to examine the antihyperglycemia activity of ethanol extract of 70% on surian bark and leaves on diabetic rats induced with streptozotocin based on body weight, and fasting blood glucose level. Consist of 28 rats are grouped into 7 groups namely normal, negative control, positive control which given glybenclamide with a dose of 3.22 mg/kg bw, bark extract with dose of 150 mg/kg bw, bark extract with a dose of 300 mg/kg bw, leaf extract with dose 150 mg/kg bw and leaf extract with dose 300 mg/kg bw. Diabetogenic mechanisms was conducted with intraperitoneal injection of streptozotocin at dose of 50 mg / kg bw. This research was conducted experimentally using complete randomized design (RAL) to analyze the results obtained. Bark extract with a dose of 150 mg/kg bw had a better antihyperglycemia activity compared to the other groups which was showed by the decrease of blood glucose level percentage of 72.83% and this group also had ability to maintain body weight was better than the other groups as well as stable feed consumption during research process.